If it's not what You are looking for type in the equation solver your own equation and let us solve it.
16b+9=b-411
We move all terms to the left:
16b+9-(b-411)=0
We get rid of parentheses
16b-b+411+9=0
We add all the numbers together, and all the variables
15b+420=0
We move all terms containing b to the left, all other terms to the right
15b=-420
b=-420/15
b=-28
| 3c-20=c/2 | | p/5=4p-57 | | 14x+9=x-368 | | 2g+-9.16=0.84 | | 1+12x=3(10x+1)+x | | y+255=-8y-6 | | a/2=5a-63 | | 25/75=x/3 | | z/5=5z-216 | | 6x+2/4=6x/7+1 | | y+244=-5y-8 | | 2/5(5x-10)-(3x-1)=-3+4x-5x | | -214=-5c-4 | | -15+9x=2(24x+40)+x | | 3x^2-42x+138=0 | | d/2=5d-27 | | c-214=-5-4 | | n-22=-3n-6 | | z/2+-6.57=-3.6 | | y-339=9y-3 | | -n+8=n+67 | | 4b-88=b/3 | | 7+5x=3(10x+28)+x | | 2(r-3)=-4(4+2r) | | 9x-4=x+172 | | x+289=-8x-8 | | 3-4z=7 | | h+30.67=-1.1h+4 | | x/6=3x-102 | | -7c+7=c+207 | | 7x+(-1)=8x+22 | | (27/8)^-3x=81/16 |